'If You Go Down to the Woods Today...': Spirituality and the Eco-Protest Lifestyle - Letcher, Andy (Journal for the study of religion, nature and culture, 2002)
Emerging from the anti-road protests which marked the 1990s, Eco-Paganism is a collective term for the diverse set of de-traditionalised, but Pagan-like, spiritualities found within road-protest culture. Whilst the actions, and direct-action, of protesters may not always appear outwardly to be religious, many protesters are motivated by their religious convictions such as the paramount belief in the sanctity of nature. The protest lifestyle, involving an immersion in nature through living outdoors and sleeping in treehouses, reinforces these convictions. These sentiments, and the anguish felt by practitioners as they engage in environmental struggle, find expression through spontaneous rituals. This article provides an overview of the protest lifestyle, suggesting ways in which it informs Eco-Pagan religiosity. An example of a typical ad-hoc religious ritual is provided.